The Association of BMI and TSH Levels with IVF/ICSI Outcomes - Soudabeh Sabetian; Zeinab Montaseri; Fatemeh Dadgar; Zahra Esfandiari; Sedighe Foruhari; Bahia Namavar Jahromi (Journal of Infertility and Reproductive Biology, 2025)
Objective: This study aimed to investigate the relationship between thyroid-stimulating hormone (TSH) levels, body mass index (BMI), and the success or failure of in vitro fertilization (IVF), as well as pregnancy outcomes in women undergoing IVF/ICSI treatment. Methods: In this case-control study, data were collected from 278 infertile couples referred to infertility centers affiliated with Shiraz University of Medical Sciences between 2016 and 2023. Demographic variables, hormone levels, TSH, BMI, and additional factors such as infertility duration and varicocele status were analyzed. Statistical analysis was conducted using SPSS software. Results: Of the participants, 137 achieved successful IVF outcomes. BMI, TSH levels, and hypothyroidism were not significantly correlated with IVF/ICSI success or live birth rates. Secondary infertility cases demonstrated higher success rates, and men with untreated varicocele were linked to better IVF outcomes. Conclusion: BMI and TSH levels showed no significant association with IVF success or live birth outcomes. However, secondary infertility and untreated male varicocele were associated with improved pregnancy results. Further research with larger samples and detailed sub-categorization of infertility causes is recommended.